Choosing Optimal Seed Nodes in Competitive Contagion - Kumar, Prem; Verma, Puneet; Singh, Anurag; Cherifi, Hocine (Frontiers in Big Data, 2019)
In recent years there has been a growing interest in simulating competitive markets to find out the efficient ways of spreading a product or an ideology. Along this line, we consider a binary competitive contagion process where two infections, A and B, interact with each other and diffuse simultaneously in a network. We investigate which is the best centrality measure to find out the seed nodes a company should adopt in the presence of rivals so that it can maximize its influence. These nodes can be used as the initial spreaders or advertisers by firms when two firms compete with each other. Each node is assigned a price tag to become an initial advertiser which varies according to their importance in the network. Considering their fixed budgets, they initially determine the payoff of their products and the number of their initial seeds in a network. Under this setting, we study the question of whether to choose a small number of influential nodes or a larger number of less influential nodes.